Does Bank Health Reach the Market? Evidence from Profitability-Driven Valuation in FX Banks - Surayya, Surayya; Bidin, Cici Rianti K; Anisah, Anisah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines how bank soundness translates into profitability and market valuation in foreign exchange national private commercial banks in Indonesia. Its core contribution lies in reframing risk-based bank assessment as a transmission mechanism, showing how liquidity discipline and cost efficiency shape firm value primarily through profitability rather than through isolated governance or capital indicators. Using panel data from eight banks over 2018–2023 and moderated regression analysis, the findings show that liquidity management, governance quality, and operating efficiency significantly influence return on assets, while credit risk and margin structure do not exert direct effects. Profitability, in turn, significantly enhances firm value and selectively strengthens the impact of liquidity on valuation. These results imply that market confidence rewards banks that convert balance-sheet discipline into sustained profitability, underscoring the strategic importance of efficient intermediation for investors and bank managers alike.